PENGARUH LATIHAN ABC DRILL TERHADAP KELINCAHAN DRIBBLING PEMAIN SSB PERISAI MUDA BUNGO - Febriyoni (Master of Physical Culture and Recreation in Nusantara, 2025)
This research was motivated by players' failure to maximize their speed during training and the lack of varied speed training methods. The objective was to determine whether the ABC Drill training method had an effect on the speed dribbling of SSB Perisai Muda Bungo players. This research used an experimental approach with a quantitative approach. The population in this study was 60 students aged 12-15 at SSB Perisai Muda Bungo. The sampling technique used was purposive sampling. The sample size was 20 students. Data analysis techniques used were normality testing and hypothesis testing. The results of this study indicate that ABC Drill training can affect dribbling speed in soccer games at SSB Perisai Muda Bungo. This is evident from the average pretest time of 40.31 seconds and the average posttest time of 19.32 seconds. In the prerequisite test, the hypothesis test used the Wilcoxon test with an Asymp. Sig. (2-tailed) value of 0.000 < 0.05. Therefore, Ha is accepted and H0 is rejected. Based on the research, it can be concluded that there is a significant effect of ABC Drill training on dribbling speed in soccer games at SSB Perisai Muda Bungo.